2018
DOI: 10.1007/s00270-018-2001-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Needle Positioning Accuracy of a Light Puncture Robot Under MRI Guidance: Results of a Clinical Trial on Healthy Volunteers

Abstract: LPR accuracy in the deployment of a sham needle inside the MRI tunnel and its setup time are promising. Further studies need to be conducted to confirm these results before clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As the thinnest scanning thickness of our CT is 1 mm, the radius of sphere target was set as 1 mm to reduce the influence of scanning. When compared with other equipment[ 21 - 24 ], the results of our research are promising given the same accuracy of the navigation robot. For short- and medium-distance targets, the position errors were 1.7 ± 0.9 mm and 2.4 ± 1.0 mm, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…As the thinnest scanning thickness of our CT is 1 mm, the radius of sphere target was set as 1 mm to reduce the influence of scanning. When compared with other equipment[ 21 - 24 ], the results of our research are promising given the same accuracy of the navigation robot. For short- and medium-distance targets, the position errors were 1.7 ± 0.9 mm and 2.4 ± 1.0 mm, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…The cadaver study showed the feasibility of using the robotic device for accurate needle placement under intraoperative MRI guidance. Achieved needle placement accuracy of 2.07 mm with the robotic assistance is better than previously reported manual (3.1 ± 1.2 mm) (Fritz et al, 2012), robot-assisted abdominal interventions (4.1 mm) (Ghelfi et al, 2018) and liver interventions (4.1 ± 3.1 mm) (Hata et al, 2016). Though the accuracy improvement is not huge, robotic system can deliver this performance irrespective of the surgeon's experience.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, Passive guidance systems lack accuracy and are sensitive to artifacts. Considering the work of robotic system other than prostate for in-bore needle intervention with the aid of passive markers under 3 T MRI for clinical testing, resulted in <5 accuracy with T1−w sequences, targeting 10 deep lesion sites of ≥5 size [141]. 2) Active guidance systems require integration of the RF-coil interventional tool, e.g., needle tip, which does not require any space co-ordinate registration.…”
Section: Needle Guidance Systemmentioning
confidence: 99%